Comparative study of antibacterial activity between Cynodon dactylon crude and solid phase extraction extracts against selected bacterial pathogens - Abdullah, Syahriel; Gobilik, Januarius; Chong, Khim-Phin (Bangladesh Journal of Pharmacology, 2014)
DOI: http://dx.doi.org/10.3329/bjp.v9i4.20616